The influence of surface EMG-triggered multichannel electrical stimulation on sensomotoric recovery in patients with lumbar disc herniation: study protocol for a randomized controlled trial (RECO). Issue 1 (December 2017) - Lener, Sara; Wipplinger, Christoph; Hartmann, Sebastian; Löscher, Wolfgang N.; Neururer, Sabrina; Wildauer, Matthias; Thomé, Claudius; Tschugg, Anja
Abstract Background Intervertebral disc degeneration is one of the most common reasons for chronic low back pain and sensomotoric deficits, often treated by lumbar sequestrectomy. Nevertheless, the prognostic factors relevant for time and quality of recovery, of the surgical procedure, relative to conservative treatment, remain controversial and require further investigation. Surface electrical stimulation (SES) may be an influential intervention, already showing positive impact on motor and sensory recovery in different patient groups. Since mechanisms of SES still remain unclear, further inquiry is needed. Methods/Design This is a prospective, monocentric, randomized, controlled clinical trial. A total of 80 adult patients suffering from a lumbar disc herniation (LDH; 40 treated surgically, 40 conservatively) are allocated in a ratio of 1:1. Patients in the treatment group will receive surface electromyography (EMG)-triggered electrical stimulation for eight weeks, whereas patients in the control group will not obtain any additional treatment. The primary outcome parameter is defined as the cold detection threshold (CDT), determined by quantitative sensory testing (QST), 24 months after intervention. Secondary outcome parameters include the inquiry of sensory nerve function by two-point discrimination and QST, the assessment of motor nerve function by manual muscle testing, and validated scales and scores. These include: the Oswestry Disability Index (ODI) and the Core Outcome Measures Index (COMI) assessing the domains pain, back-specific function, work disability, and patient satisfaction; the EQ-5D investigating the patient's generic health status; the painDETECT questionnaire (PD-Q) to identify neuropathic pain components; and the Beck Depression Inventory (BDI) to assess severity of depression. Moreover, neurological status, pain medication usage, and blood samples (CRP, TNFα, IL-1β, IL-6) will be evaluated. Study data generation (study site) and data storage, processing, and statistical analysis are clearly separated. Discussion The results of the RECO study will detect the effect of EMG-triggered multichannel SES on the improvement of mechanical and thermal sensitivity and the effect on motor recovery and pain, associated with clinical and laboratory parameters. Furthermore, data comparing surgical and conservative treatment can be collected. This will hopefully allow treatment recommendations for patients with LDH accompanied by a sensomotoric deficit. Trial registration ISRCTN, ISRCTN12741173 . Registered on 15 January 2017.